Pendampingan Penyusunan Rencana Kerja Sekolah Bagi Kepala Sekolah, Guru dan Komite Sekolah di Kabupaten Polman Sulawesi Baratwesi Barat - Torro, Supriadi; Manda, Darman; Ridha, Rasyid; Patahuddin, Patahuddin; Paramitha Darmayanti, Dyan (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Preparing school work plans is an important part of effective educational management. The aim of this training is to increase participants' understanding and skills in preparing work plans that focus on goals and measurable results. The training participants consisted of school principals, teachers and school committee members from Polman Regency, West Sulawesi. Training is carried out by identifying potential obstacles in developing work plans, including differences in knowledge levels, limited resources, and collaboration challenges between related parties. Through a participatory and interactive approach, participants are invited to engage in discussions, case studies and practical exercises to overcome these obstacles. The impact of this training is increasing participants' understanding of the importance of work plans as a strategic tool in educational management, as well as mastering practical skills in developing comprehensive and measurable work plans. Collaboration among participants is also enhanced to ensure active participation and shared responsibility in implementing the work plan. It is hoped that this training will have a positive impact on improving the quality of education and performance of schools/madrasahs in Polman Regency. The experiences and lessons learned from this training can also become the basis for developing similar activities in the future